Sistem Pendukung Keputusan Pemilihan Pegawai Terbaik Menggunakan Metode Simple Additive Weighting (SAW) Pada PT. Japung Zain Logistic - Istiyani Nani; Taufik Baidawi (Journal Of Informatics And Busisnes, 2024)
Japung Zain Logistic is a logistics company that offers delivery services for partner companies to destinations within the city, Java, Sumatra, Bali, and throughout the archipelago. To improve employee performance, PT. Japung Zain Logistic conducts monthly evaluations where the leadership assesses the performance of their subordinates. The employee with the highest evaluation score is considered the best employee. Therefore, the author has taken steps to design a decision support system. Through the application of the SAW method, it is expected that the developed decision support system can become a more effective tool in supporting the decision-making process related to selecting the best employee at PT. Japung Zain Logistic. After performing calculations using the SAW method, as shown in Table 10 above, Oktiliani received the highest rank with a score of 0.80 or 80%, while Darsono received the lowest rank with a score of 0.41 or 41%. This system allows decision-makers to evaluate employees promptly and quickly, where previously HRD and the leadership faced difficulties in selecting the best. As a result, this system can provide direct reports.